Use of Quantum Computers with AI Integration for Drug Discovery - Yadav, Sanyog Virendra (Journal of Advanced Research in Information Technology, Systems and Management, 2025)
The merging of artificial intelligence and quantum computing could be recognised as a revolutionising method in the field of drug discovery. The traditional process of drug discovery has been considered as expensive, consisting of much more human power and also time-consuming. Currently AI is being used to detect drugs. But the main need for today's world is to carry out these processes at a fast pace and with precision. Hence, Quantum computing could be proven to be a helping hand for AI, which would not only make the procedure faster but also come out with phenomena which are unknown to mankind. The research paper revolves around the topic and tries to point out the significance of this combination. The paper discusses the people's understanding of this topic and their responses on the survey related to the topic. The paper tries to represent research based on surveys of 2 kinds i.e. the information technology and pharmaceutical field. Gathering responses from both the fields and what they think about this technology and how much they think it would be favourable in the coming future.